Writing Voices of Poetic Vulnerability: A Phenomenological Inquiry into Writing Voices that Resurrect the Wounded Self - Liddell, Freya Rowena (Curtin University, 2018)
I explore time and its linear impression on our lived world to find ways for calling on our past, through writing, to reconstitute our memories and voices and to discover as yet unexplored narratives of our lives. The thesis engages in a hermeneutics of vulnerability that unlocks the narratives that lie behind journal entries and transcends traditional boundaries in ways that traverse subjective layers of self where compassion lies at the centre of embodied understanding.